Optimization of Positive End-Expiratory Pressure in Patients with Acute Respiratory Distress Syndrome Caused by Direct and Indirect Damaging Factors - V. V. Moroz; A.V. Vlasenko; V. N. Yakovlev; V. G. Alekseyev (Общая реаниматология)
Objective: to study the clinical efficiency of undifferentiated and differentiated use of escalation and de-escalation procedures for optimizing positive end-expiratory pressure (PEEP) during mechanical ventilation in patients with acute respiratory distress syndrome (ARDS) resulting from direct and indirect damaging factors. Subjects and methods. During a prospective study, 24 examined patients (16 men, 8 women; their age was 22 to 65 years) with ARDS of different genesis were divided into 2 groups. Group A (n=11; 7 men, 4 women) and Group B (n=13; 9 men, 4 women) included patients with ARDS arising from both direct (gastric content aspiration, blunt chest injury with lung contusion, and acute bilateral bacterial pneumonia) and indirect (abdominal sepsis, severe nonthoracic injury, and acute massive blood loss) damaging factors. The results of treatment via differentiated or undifferentiated, according to the cause of ARDS, use of escalation and de-escalation procedures for PEEP optimization were assessed in Groups A and B patients. Results. The differentiated, according to the cause of ARDS, use of escalation and de-escalation procedures for PEEP optimization makes it possible to more effectively improve the parameters of pulmonary gas exchange and biomechanics and to reduce the length of respiratory support and stay in the intensive care unit, the incidence of ventilator-associated pneumonia, and mortality rates in patients with ARDS resulting from direct and indirect damaging factors. Conclusion. It is advisable to apply the differentiated, according to the cause of ARDS, approach to choosing escalation or de-escalation procedures to optimize PEEP in patients with ARDS of different genesis. Key words: acute respiratory distress syndrome, direct damaging factors, indirect damaging factors, mechanical ventilation, positive end-expiratory pressure, escalation PEEP optimization procedure, de-escalation PEEP optimization procedure, lung opening manoeuver.